The diversity, dynamics, and culturability of bacterial and fungal communities present in warm-season pasture grass seeds - Rens R. T. van Essen; Rens R. T. van Essen; Jatinder Kaur; Jatinder Kaur; Tongda Li; Tongda Li; Ross C. Mann; Tim I. Sawbridge; Tim I. Sawbridge (Frontiers in Microbiology)
A rapidly changing climate has resulted in increasing challenges for farmers. This has led to an increase in demand for beneficial microbes to help fight these challenges faced by farmers, improving crop production under harsh conditions. Increasing temperatures caused by the changing climate will also affect the dairy industry in temperate climates around the world. This has resulted in an increasing importance of warm-season pasture grasses to fill the feed gaps left by the affected temperate grasses. In this study, we assessed the microbial communities present in commercially available warm-season pasture grass seeds. We utilised amplicon metagenomics to profile and compare the bacterial and fungal communities of seeds from three different genera of warm-season pasture grasses. Microbial isolations have also been performed to assess the culturability of the seed microbiome. Significant differences in drivers of bacterial and fungal communities within warm-season pasture grass seeds were observed. In addition, most of the bacteria present in high abundance were found to be culturable, while a relatively lower percentage of abundant fungi were culturable. Analysis of the bacterial communities showed considerable variation between different distributors, possibly driven by differing seed processing methods. This variation indicates that the bacterial communities could be manipulated by providing different bacteria to the seed to promote plant growth under different conditions. In contrast, the fungal communities were more strongly driven by the genetics of the respective host genera. This suggests that differences in fungal strain levels could be exploited for modification of fungal microbiome effects.